Monitoring Baby's Motor Development Through Android-Based Baby GYM Application - Nurhayati Nurhayati; Masita Masita; Husnul Khatimah; Tutik Iswanti; Jusuf Kristianto (Jurnal Health Sains, 2022)
Background: The process of growth and development of neonates requires a sensory-motor stimulus, one of which is the ability of parents. In total, neonates still depend on the environment, especially the family as the first environment in their lives. Touch is one of the stimulation sensations in neonates that can be done at birth by parents or family.Baby Gym can stimulate and optimize baby's growth and development from an early age. Neonatal period has four aspects of development, namely, gross motor, fine motor, personal social, and language. Baby Gym can be done by parents or those closest to the baby, but it should be done by the mother, because the baby is used to the touch his mother does.Objective: This study aims to determine the baby's motor development through the baby gym application.Methods: This type of research is a quasi-experimental design with a pretest and posttest design with a control group design. The population taken in this study were mothers who had babies aged 3-12 months at the Puskesmas in the South Tangerang City area. The sample size for this study were 31 respondents in the intervention and control groups, so that the total sample was 62 people. The sampling technique in this study used the purposive sampling method. Data analysis using Wilcoxon and Man Whitney test and multivariate analysis using multivariate multiple logistic regression.Research Results: The Wilcoxon statistical test value showed that there was a significant difference in the average motor development before and after the baby gym application intervention was given to the mother (p value = 0.000). The results of the analysis using Mann Whitney found that there was a significant effect of using the baby gym application on the motor development of infants in the intervention group compared to the control group with p = 0.000 (p < 0.005).Conclusion: there is an effect of using the baby gym application on the baby's motor development. So as to provide recommendations for the use of the Baby gym application to help stimulate the development of the baby and also to establish affection between mother and baby.